Physiological and productive response of tomato in a reel modified NFT system - AyalaContreras, Carmen Alicia; González-Fuentes, José Antonio; Zermeño-González, Alejandro; Benavides-Mendoza, Adalberto; Peña-Ramos, Fidel Maximiano; Hernández-Mauriri, José Alfredo (Ecosistemas y Recursos Agropecuarios, 2022)
Tomato production in protected systems employs low-growing varieties, indeterminate to achieve greater productivity leading to long stems in advanced stages. For this reason, a modified NFT technique is proposed by using a reel to coil the stem that will generate adventitious roots and a productive stem of 2 meters, compared to a control in a 20 L bag of substrate (peat). The objective was to evaluate the physiological and productive response of the tomato crop established in an NFT system modified reel type, under a completely random design. The results indicate that there were significant differences between treatments such as: physiological variables, efficiency intrinsic and quantum, number of fruits per plant, fruit weight, equatorial diameter and yield except for length and diameter of stem,  length of leaf, polar diameter of fruit and weekly growth. The reel system is an alternative for the production of greenhouse tomato.
Keywords: hydroponics, yield, photosynthesis, development, Solanum lycopersicum L.